Endosymbiosis in trypanosomatid protozoa: the bacterium division is controlled during the host cell cycle - Catta-Preta, Carolina M. C.; Brum, Felipe L.; da Silva, Camila C.; Zuma, Aline A.; Elias, Maria C.; de Souza, Wanderley; Schenkman, Sergio; Motta, Maria Cristina M. (Frontiers in Microbiology, 2015)
Mutualism is defined as a beneficial relationship for the associated partners and usually assumes that the symbiont number is controlled. Some trypanosomatid protozoa co-evolve with a bacterial symbiont that divides in coordination with the host in a way that results in its equal distribution between daughter cells. The mechanism that controls this synchrony is largely unknown, and its comprehension might provide clues to understand how eukaryotic cells evolved when acquiring symbionts that later became organelles. Here, we approached this question by studying the effects of inhibitors that affect the host exclusively in two symbiont-bearing trypanosomatids, Strigomonas culicis and Angomonas deanei. We found that inhibiting host protein synthesis using cycloheximide or host DNA replication using aphidicolin did not affect the duplication of bacterial DNA. Although the bacteria had autonomy to duplicate their DNA when host protein synthesis was blocked by cycloheximide, they could not complete cytokinesis. Aphidicolin promoted the inhibition of the trypanosomatid cell cycle in the G1/S phase, leading to symbiont filamentation in S. culicis but not in A. deanei. Treatment with camptothecin blocked the host protozoa cell cycle in the G2 phase and induced the formation of filamentous symbionts in both species. Oryzalin, which affects host microtubule polymerization, blocked trypanosomatid mitosis and abrogated symbiont division. Our results indicate that host factors produced during the cell division cycle are essential for symbiont segregation and may control the bacterial cell number.